1970
DOI: 10.1364/josa.60.001489
|View full text |Cite
|
Sign up to set email alerts
|

Photodetection of Low-Level Radiation through the Turbulent Atmosphere*

Abstract: Photoelectron-counting distributions are obtained for stochastic light that is caused to scintillate by passage through a random medium. The result is applied specifically to transmission of amplitude-stabilized radiation, with and without independent additive background, and of chaotic radiation, through the turbulent atmosphere. The counting distribution is found to broaden markedly and its peak occurs at decreasing count numbers for increasing turbulence. The cases studied here are of particular interest fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

1971
1971
2017
2017

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 13 publications
1
41
0
Order By: Relevance
“…The results (5) and (6) are valid in the weak-perturbation limit of small D . Experiments by Gracheva and Gurvich4 indicated that the log-normal distribution is reasonably accurate for u2 < 0.3.5 Using (6) with X = 772 nm and L = 10 km, their results would imply that the log-normal distribution should be accurate for C i < 9.8 x mm2l3.…”
Section: ( T ' )mentioning
confidence: 74%
“…The results (5) and (6) are valid in the weak-perturbation limit of small D . Experiments by Gracheva and Gurvich4 indicated that the log-normal distribution is reasonably accurate for u2 < 0.3.5 Using (6) with X = 772 nm and L = 10 km, their results would imply that the log-normal distribution should be accurate for C i < 9.8 x mm2l3.…”
Section: ( T ' )mentioning
confidence: 74%
“…More accurate estimates of the dependence of freespace qkd performance on source characteristics and on the communication distance d can be obtained by applying existing analyses of atmospheric effects on optical signals [14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…29 / October 10 2017 / Applied Opticsprocess in the Gm-APD. Therefore, when the turbulence effects are added, the probability with m primary electrons fired in the Gm-APD during the integration times t 1 and t 2 is [7,9] PmjK…”
Section: Research Articlementioning
confidence: 99%
“…When the turbulence effects are added, a reducing detection performance will be produced, the influence of the turbulence effects on the photon flux can be modeled as a modulation of the mean irradiance, the statistics of the modulated echo photons is assumed to obey the lognormal distribution and be statistically independent of the echo photon detection, and the detection probability of the echo photons with turbulence effects is considered to obey the modulated Poisson distribution [7][8][9]. Cumulative pulse detection has the ability to improve the target detection probability and restrain the false alarm probability effectively [1,2,10,11].…”
Section: Introductionmentioning
confidence: 99%